Technology entrepreneurship, innovation and intrapreneurship: Managing entrepreneurial activities in technology-intensive environments - Brem, Alexander; Borchardt, Jens (Handbook of Research on Techno-Entrepreneurship, 2014)
Today there is little doubt that the modern economy is driven by firms which capitalize on change, challenge and technology. The technology sector represents an important share of the economy of every industrial nation, for example, in the United States more than one-third of the gross national product and about half of the private-sector spending on capital goods are related to technology. Other examples are Japan and Germany; they occupy the worldís second and third places, respectively, as measured by patents granted in the year 2011: (1) United States: 121,261 patents granted, (2) Japan: 48,256 patents granted, (3) Germany: 12,968 patents granted (Marketline, 2012). The examples and figures suggest a high capacity for innovation, or rather a high accumulation of start-ups and entrepreneurs, especially in the technology sector. Technology and similar high-growth enterprises are both an important part of our worldís economic growth as well as the place where young entrepreneurs realize their dreams. Technology involves devices, artefacts, processes, methods, tools and materials that can be applied to industrial and commercial intentions (Byers et al., 2011). As stated, research and innovation in technology are drivers of economic growth and social change. In order to be fruitful, they need an innovative business environment and good knowledge gained from science. Essential for the transformation of research results into products and services are research institutions and a good know-how and technology transfer.